Pengaruh Kompensasi terhadap Kinerja Guru di SD Negeri 071078 Hiliweto Gido - Waruwu, Nita Ingati; Hulu, Fatolosa; Halawa, Odaligoziduhu; Bate’e, Maria Magdalena (Jurnal EMT KITA, 2025)
Teachers have a crucial role in improving the quality of education in educational institutions. As educators, teachers are responsible for carrying out their duties optimally to support the learning process. One of the factors that influences teacher performance is the reward for work results in the form of compensation, either in the form of salary, allowances, or other facilities. However, there are several obstacles, such as low additional income, honorary workers who have not received salaries, and minimal teaching quality due to limited compensation. This study aims to analyze the effect of compensation on teacher performance at SD Negeri 071078 Hiliweto Gido. The research method uses a quantitative approach with data analysis through SPSS version 26. The research sample consisted of 33 respondents, including all permanent teachers and honorary workers at the school. The results of the study showed a significant effect of compensation on teacher performance, with a calculated r value of 0.742, greater than the r table of 0.361. The average compensation score was 6.30 and performance was 7.16, both of which are in the good category. These findings indicate that compensation plays an important role in increasing teacher motivation and productivity in carrying out their duties.